China's commercial aircraft industry : not so fast - Bitzinger, Richard A. (2013)
China is currently pursuing a very ambitious commercial aircraft development programme, including the production of two medium-size airliners. However, it faces considerable - perhaps even insurmountable - barriers to breaking into this tough and demanding business.